RAISING AWARENESS OF THE LAW ON LIABILITY FOR DAMAGES RESULTING FROM DEFAMATION ON SOCIAL MEDIA - Bintang Al Nasha; Ihfa Aulia; Muasa Saputra; Siska Siska; Uswatun Hasanah (Hukum tata Negara/Siyasah, 2026)
Abstract:The development of information technology has brought major changes in the communication patterns of society through social media. On the one hand, social media provides convenience in the dissemination of information and social interaction, but on the other hand, it also opens opportunities for misuse, including acts of defamation. This research aims to increase students’ legal understanding regarding liability for compensation due to defamation on social media as well as to provide education about legal boundaries in expressing oneself in the digital space. The research method used is an educational socialization approach through interactive counseling, discussions, and case studies with students of SMK Negeri 7 Kota Serang. The results of the research show that participants’ understanding of legal protection of honor and reputation on social media increased after the implementation of the activities. This research also found that defamation on social media gives rise to legal consequences in two domains, namely criminal law based on the provisions of the Criminal Code and the Electronic Information and Transactions Law (ITE Law), as well as civil law through the mechanism of lawsuits for unlawful acts based on the Civil Code. Civil liability may take the form of an obligation to pay compensation for material and immaterial losses suffered by the victim. Therefore, the improvement of digital legal literacy is very important in order to build public awareness, especially among students, so that they are able to use social media wisely, responsibly, and in accordance with applicable legal provisions. Keywords: Defamation, Social Media, Civil Liability, Compensation, Digital Legal Literacy..